2019
DOI: 10.3390/info10120384
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Mobile Payment Acceptance in China: An Empirical Investigation

Abstract: With the rapid development of mobile technologies in contemporary society, China has seen increased usage of the Internet and mobile devices. Thus, mobile payment is constantly being innovated and is highly valued in China. Although there have been many reports on the consumer adoption of mobile payments, there are few studies providing guidelines on examining mobile payment adoption in China. This study intends to explore the impact of the facilitating factors (perceived transaction convenience, compatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 84 publications
8
42
0
2
Order By: Relevance
“…In contrast, the current study implied that the adoption of Fintech payment services is not influenced by the surrounding, but it comes from a voluntary action to adopt a technology. This finding is like several studies such Alalwan et al (2017) and Chen et al (2019), where individuals seemed to be less interested in the recommendations and attitudes of their reference groups (i.e., family, friends, colleagues) regarding the adoption of technology. It is because the adoption of technology is a voluntary action and is often conducted solo.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, the current study implied that the adoption of Fintech payment services is not influenced by the surrounding, but it comes from a voluntary action to adopt a technology. This finding is like several studies such Alalwan et al (2017) and Chen et al (2019), where individuals seemed to be less interested in the recommendations and attitudes of their reference groups (i.e., family, friends, colleagues) regarding the adoption of technology. It is because the adoption of technology is a voluntary action and is often conducted solo.…”
Section: Discussionsupporting
confidence: 85%
“…The information and encouragement provided by the surrounding people play a dynamic role in contributing to the understanding of the consumer as well as influencing one's behavior in accepting the technology such as Fintech payment services. While some researchers have found social influence as the most salient predictor (Abrahão et al, 2016;Abdullah et al, 2018;Keng-Soon et al, 2019;Yahaya & Ahmad, 2019), others have found that social influence had no significant influence (Chen, Chen, & Chen, 2019;Alalwan et al, 2017). Social influence cannot be substantial if changes are just implemented.…”
Section: Social Influencesmentioning
confidence: 99%
“…According to results of the research study of Tse et al (2019), more attention has to be paid to security factors, while the main factors identified as affecting customers' adoption of m-payment products are risk issues, age and gender, and finally the type of mobile payment platforms. Furthermore, results of Harris et al (2019) review analysis supported the previous study from Dahlberg et al (2015). In specific, they also confirmed that the TAM and UTAUT/UTAU2 models have dominated the investigations into m-payment systems' adoption.…”
Section: Umbrella Reviewsupporting
confidence: 81%
“…. 2015;Chen et al 2019; Park et al 2019a,b;Sinha et al 2019 RQ4: What constructs/ factors are enablers or inhibitors regarding the adoption of m-payment?…”
mentioning
confidence: 99%
“…Looking at the practical significance, the emergence of m-wallet has become a disruptive technology as it alters the basis of competition [ 24 ]. This is especially true in the hospitality industry, as m-wallet users could gain additional values such as cash-back returns when making payments through m-wallet [ 25 , 26 ]. Also, owing to the COVID-19 pandemic that demands everyone to practice a “new normal”, m-wallet is encouraged over cash in making payments to avoid infection [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%